Vermicompost of Cow Dung and Goat Manure to Increase N Absorption, Mustard (Brassica rapa L) Growth and Yield in Ultisols - Tulus Roy Rasdian Purba; R. Teguh Adi Prasetyo; Bambang Gonggo Murcitro; Abimanyu Dipo Nusantara; Eko Suprijono (TERRA : Journal of Land Restoration, 2021)
This study aims to obtain N levels and N absorption as well as the growth and yield of mustard plants in ultisol soilapplied vermicompost cattle or goats. This research has been conducted from April 2020 – May 2020. Implementation of research on UNIB garden and Soil Science Laboratory of Faculty of Agriculture, University of Bengkulu. This study used a Complete Randomized Design (CRD) with a single factor consisting of 7 treatments, namely control, vermicompost cow dung with a dose of 10 tons ha-1 , 20 tons ha-1 , and 30 tons ha-1 , and vermicompost goat manure with a dose of 10 tons ha-1 , 20 tons ha-1 , and 30 tons ha-1 . The results showed that the administration of vermicompost cow dung at a dose of 30 tons ha-1 gave the best results for N tissue levels, N absorption, and mustard results in Ultisol. The same result was obtained from the administration of vermicompost goat manure at a dose of 20 tons ha-1 .